Is Comprehensive Income Superior to Net Income in Equity Valuation? Evidence from the Capital Market of Kuwait - Elshamy, Mostafa A.; Alyousef, Husain Y.; Al-Mudhaf, Jassem (Journal of Applied Business Research, 2019)
The study examines whether comprehensive income numbers reported under International Financial Reporting Standards (IFRS) have value relevance over net income in equity valuation. We use a sample of firms that are listed in Kuwait Stock Exchange from banking, investment, real estate, industrial, basic materials, telecommunications, consumer services, oil & gas and health care sectors during the years 2012-2015.The study applies a methodology used by Collins, Maydew and Weiss (1997) that is based on Ohlson (1995) equity valuation model and Theil (1971) technique to measure and compare the relative and the incremental explanatory power of comprehensive income and net income. The study provides evidence that comprehensive income is not superior to net income in equity valuation. Reporting other comprehensive income gains and losses as elements of the income statement produces a measure of earnings that decreases the explanatory power of the valuation model; decreases the incremental information content of earnings. Other comprehensive income gains and losses when added as an explanatory variable to the valuation model did not enhance significantly its explanatory power.The results we obtained supports the current requirement by the IFRS and US GAAP of deferring other comprehensive gains and losses and contributes to the literature on the value relevance of other comprehensive income gains and losses in emerging capital markets.
Keywords: business; research; Equity Valuation; Reporting Comprehensive Income; Value Relevance; Other Comprehensive Income Gains and Losses